Normal Population Reference Values for the Oxford and Harris Hip Scores – Electronic Data Collection and its Implications for Clinical Practice. Issue 4 (July 2017) - McLean, James M.; Cappelletto, Jacob; Clarnette, Jock; Hill, Catherine L.; Gill, Tiffany; Mandziak, Daniel; Leith, Jordan
Background: The aim of this study was to assess whether the Harris Hip Score (HHS) and the Oxford Hip Score (OHS) were comparable in normal, healthy, pathology-free individuals of different age, gender, ethnicity, handedness and nationality. The purpose of this study was to establish normal population values for the HHS and OHS using an electronic data collection system. Methods: 317 Australian and 310 Canadian citizens with no active hip pain, injury or pathology in the ipsilateral hip corresponding to their dominant arm, were evaluated. Participants completed an electronically-administered questionnaire and were assessed clinically. Chi-square tests, Fisher's exact test and Poisson regression models were used where appropriate, to investigate the association between hip scores, ethnicity, nationality, gender, handedness and age. Results: There was a statistically significant association between the OHS and age (p<0.0001) and the HHS and age (p = 0.0006); demonstrating that as age increased, normal hip scores decreased. There was no statistically significant association between the HHS and gender (p = 0.1389); or HSS and nationality, adjusting for age (p = 0.5698) and adjusting for gender (p = 0.6997). There was no statistically significant association between the OHS and gender (p = 0.1350). Australians reported a statistically significant 4.2% higher overall OHS value compared to Canadians (p = 0.0490). There was no statistically significant association between the OHS and nationality in age groups 18-79 years. Participants >80 years reported a statistically significant association between the OHS and nationality (p<0.0001). Conclusions: Studies using an electronic control group should consider differences in gender, age, ethnicity and nationality when using the HHS and OHS to assess patient outcomes. This study has established an electronic, normal control group for studies using the HHS and OHS. When using the OHS, the control group should be sourced from the same country of origin. When using the HHS, the control group should be sourced from a pre-established control group within a database, without necessarily being sourced from the same country of origin.